ENHANCING NURSING STUDENTS’ READING COMPREHENSION USING GIST STRATEGY IN NURSING ACADEMY (AKPER) PRIMA JAMBI 2016 - Silvia, Resi (SCIENTIA JOURNAL, 2017)
This research is conducted in order to enhance nursing students’ reading comprehension usingGIST Strategy. Appointing to the importance of schema theory in reading, this present studyinvestigates the use of Generating Interactions between Schemata and Text (GIST) to improvethe students reading comprehension at third semester of nursing students in AKPER Prima. Thisresearch used Classroom Action Research (CAR) which is conducted to solve the students'problem in English reading. Two cycles were conducted in which each cycle consist of planning,acting, observing, and reflecting. The data were gathered through qualitative and quantitativedata. The qualitative gained by analysing the field note, observation sheet and interview. Thenquantitative data were obtained from the students' reading score of cycle I and cycle II. Thefinding of this research indicated that the implementation of GIST Strategy was success full sincethere is an improvement in students' reading comprehension. The finding showed significantimprovement in students' reading comprehension. It is suggested that GIST Strategy can beimplemented in teaching reading in order to enhance students in learning English reading.